The Media of Washatiyah Dakwah in Quranic Exegesis Study - Andri Nirwana; Hayati Hayati; Muhammad Ridhwan (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
the fact explains that the Islamic media in the late 70s-90s tended to be provocative, brave, straightforward and resolute in raising issues and themes that were sensitive and offensive to ethnicity, religion, race and interfaith (SARA) and dared to carry ideology, exclusivist and fanaticism that strong against Islam, even though at that time media freedom was very limited. After the 90s the media became free in handling and publishing. Unfortunately this condition is not exploited by Wasatiyah Islamic Media. This media tends to sink due to competition in the media business. The decline of wasatiyah Islamic Media was due to imperfect management. The obstacles in presenting news that are fast, easy and inexpensive require good management. Another challenge is how to provide intelligent reading that follows the development of increasingly intelligent humans and provides a binding and enlightening impression. As a result of the deterioration of management, other Islamic media have the opportunity to spread the news of hate speech and hoaxes. To this problem we use the Thematic Interpretation Method of the Qur'an to provide concepts and descriptions of the Qur'an based Wasatiyah media. The results of this study stated that Wasatiyah Islamic Media must understand the Counter-Radical Narrative Narratives spread by other media. So in providing comments and information must be based on Islam Rahmatan lil alamin. Wasatiyah Islamic Media Must understand the weaknesses of the radical media editors. Wasatiyah Islamic media must play a role and provide moderation for religious and Islamic thought in line with the Unitary State of the Republic of Indonesia. Editor of the Wasatiyah Islamic Media must depict editors who are more humane, polite, not hard, without coercion, full of tenderness and voluntarily. The results of this study have an impact on the unity and sovereignty of the Republic of Indonesia.